Association between Acute Respiratory Failure Requiring Mechanical Ventilation and the Production of Advanced Glycation End Products. (October 2020) - Edriss, Hawa; Molehin, Adebayo J; Gavidia, Rocio; Selvan, Kavitha; Nugent, Kenneth
Patients with acute respiratory failure often have hyperglycemia. Elevated glucose levels could cause acute lung injury through the production of advanced glycation end products. We measured glucose, advanced glycation end products, glycated albumin, circulating glycated hemoglobin, and soluble receptor for advanced glycation end product (sRAGE) levels on admission, at 24 hours, and at 72 hours in 40 patients with acute respiratory failure requiring mechanical ventilation. We compared these values with healthy control subjects. The mean age was 63.3±11.2 years. Fifty percent of the patients were women. Thirteen patients (32.5%) died during this hospitalization. The mean maximum glucose level on the day of admission was 215.7±171.1 mg/dL. Compared with control subjects, there was a significant reduction in advanced glycation end product levels (p=0.0001) in the patients at all 3 time points. Circulating glycated hemoglobin levels were significantly higher in patients compared with control subjects. We also observed a moderate increase in glycated albumin levels on admission and at 24 hours when compared with the control samples. Overall sRAGE levels were similar to controls, but patients with dense infiltrates on chest X-ray had increased levels compared with patients who did not have these dense infiltrates on the day of admission. Patients with acute respiratory failure requiring mechanical ventilation have decreased levels of advanced glycation end products and increased levels of circulating glycated hemoglobin. The results from this pilot study suggest that the acute stress associated with respiratory failure might create glycated proteins which could contribute to disease pathogenesis.